2002
DOI: 10.1074/jbc.m111105200
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer and Conformational Change in Complexes of Trimethylamine Dehydrogenase and Electron Transferring Flavoprotein

Abstract: The trimethylamine dehydrogenase-electron transferring flavoprotein (TMADH⅐ETF) electron transfer complex has been studied by fluorescence and absorption spectroscopies. These studies indicate that a series of conformational changes occur during the assembly of the TMADH⅐ETF electron transfer complex and that the kinetics of assembly observed with mutant TMADH (Y442F/L/G) or ETF (␣R237A) complexes are much slower than are the corresponding rates of electron transfer in these complexes. This suggests that elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
(54 reference statements)
6
25
0
Order By: Relevance
“…Recently, Parker & Engel showed that functional assemblies consisting of MCAD or sarcosine dehydrogenase (an enzyme of one-carbon metabolism which is also dehydrogenated by ETF) together with ETF, ETFD, coenzyme Q (ubiquinone) and complex III could be isolated from sonicated porcine liver mitochondria [45]. Similarly, Jones et al [46] have characterized electron transfer and conformational changes in a complex of trimethylamine dehydrogenase (EC 1.5.99.7, derived from the methylotroph Methylophilus methylotrophus) and ETF, and demonstrate that electron transfer occurs during metastable states of the complex. Further, they show that ETF undergoes a stable conformational change when it interacts with TAMDH which they term Ôstructural imprintingÕ and that this form of semiquinone ETF has an increased rate of electron transfer to the artificial electron acceptor ferricenium.…”
Section: Mitochondrial Control/integration Of Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Parker & Engel showed that functional assemblies consisting of MCAD or sarcosine dehydrogenase (an enzyme of one-carbon metabolism which is also dehydrogenated by ETF) together with ETF, ETFD, coenzyme Q (ubiquinone) and complex III could be isolated from sonicated porcine liver mitochondria [45]. Similarly, Jones et al [46] have characterized electron transfer and conformational changes in a complex of trimethylamine dehydrogenase (EC 1.5.99.7, derived from the methylotroph Methylophilus methylotrophus) and ETF, and demonstrate that electron transfer occurs during metastable states of the complex. Further, they show that ETF undergoes a stable conformational change when it interacts with TAMDH which they term Ôstructural imprintingÕ and that this form of semiquinone ETF has an increased rate of electron transfer to the artificial electron acceptor ferricenium.…”
Section: Mitochondrial Control/integration Of Systemsmentioning
confidence: 98%
“…Similarly, Jones et al. [46] have characterized electron transfer and conformational changes in a complex of trimethylamine dehydrogenase (EC 1.5.99.7, derived from the methylotroph Methylophilus methylotrophus ) and ETF, and demonstrate that electron transfer occurs during metastable states of the complex. Further, they show that ETF undergoes a stable conformational change when it interacts with TAMDH which they term ‘structural imprinting’ and that this form of semiquinone ETF has an increased rate of electron transfer to the artificial electron acceptor ferricenium.…”
Section: Mitochondrial Control/integration Of Systemsmentioning
confidence: 99%
“…This may imply a similar mechanism for the transfer of electrons from both groups of dehydrogenases to ETF. Conformational changes within the interaction domain that occur when substrate binds, however, could increase the affinity of the reduced dehydrogenase for ETF in vivo, providing an advantage for productive interactions resulting in electron transfer (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that PIG specific KO were found in various pathways towards production of methane. (Harms, 1996), and trimethylamine-corrinoid protein Co-methyltransferase (mttB) and dimethylamine/trimethylamine dehydrogenase (dmd-tmd) catalyze the synthesize of Methyl-CoM, a precursor of methane (Yang et al, 1995;Tallant and Krzycki, 1997;Jones et al, 2002;Pritchett and Metcalf, 2005 …”
Section: Functional Gene Distribution Analysismentioning
confidence: 99%